PENGARUH EPS, DER, DAN PER TERHADAP RETURN SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2014-2016 - Moh. Zainuddin arief; Budi Wahono; M. Agus Salim (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThe purpose of the research was do determines the effect ofEPS, DER and PER simultaneously or partially to stock returns on food andbeverage companies in Indonesia Stock Exchange. Research approach usedis a quantitive approach that works for test the hypothesis proposed in theresearch as wells as do answer the problem in the research.Samples taken as many as 8 food and beverage companies whichis listed on Indonesia Stock Exchange and has an active share during 2014-2016. To gaet required informatif is done data collection process throughdocumentation. For data collection methods that are done by making copiesby collecting records and records of existing companies. Research analysistool used is multiple linear analysis. Analysis results show That EPS, DER,and PER effect simultaneously on stok return. While only partially DER thatnegatively affect the stok return.Keywords : EPS, DER, PER and Stock Return